Penentuan Dosis Gamma Pada Fasilitas Iradiasi Reaktor Kartini Setelah Shut Down - Prasetyowati, Risprapti; Azam, Much.; Firdausi, K. Sofjan; B. S., Edi Trijono (BERKALA FISIKA, 2006)
Determination of gamma dose after reactor shut-down around the kartini reactor core have beeb done. The measurement was done at the Lazy Susan (Rotary Rack) and outside the reflector wall which could be used as irradiation facility. Determination of gamma dose was carried out using wide range dosimeter consisting of a Geiger muller detector end a surveymeter. Detector was directed to outside wall reflector and lazy susan through the dry irradiation facility. Measurement was done after shut down for 3 hours with power of 100 kW and interval of ± 5 minutes. The resulting dose rate in reflector wall without neutron source was 1,2 to 0,2 kR/hour and cumulative dose in a 205  minute period was 2,21 kRad. In reflector wall with neutron source was 6  to 0,2 kR/hour and cumulative dose in a 202  minute period was 2,25 kRad.  While in lazy Susan dose rate of 60 to 2 kR/hour and cumulative dose was 42,70 kRad in 203 minutes decay. Gamma decay constant in reflector wall without  neutron source was 0,008 per minute, with neutron source 0,013 per minute. While in lazy Susan gamma decay constant was 0,014 per minute. Keywords : dose, gamm, core and  reflector, reactor